ANALISIS BIAYA INVESTASI PADA PROYEK SISTEM PENGEMBANGAN AIR MINUM DI ZONA 3 KOTA TANGERANG - Muhammad Ali Mu’min (JUBISMA, 2021)
Drinking water is one of the basic human needs, so important that the 1945 Constitution in Article 33 Paragraph 3 regulates the maximum use of water for the prosperity of the people. Access to drinking water which is the SDG's target, namely 68.87% of Indonesians can be served access to safe drinking water in 2015 especially in 2019, at this time it has not been achieved. The National Medium-Term Development Plan (RPJMN) plans 100% of Indonesians to have access to drinking water by 2019. To achieve this target, additional production capacity and large distribution networks are required. it is necessary to build infrastructure that can support the increasing need for drinking water. Technical planning for the development of a Drinking Water Supply System (SPAM) in zone 3, including the construction of an intake unit, a production unit of 1,000 lps and a distribution unit.